Risk Factors Associated with Helminthic Intestinal Infection in Lurambi Subcounty, Kakamega, Kenya - Ruth W. Kiiti; Elizabeth N. Omukunda; Jackson C. Korir (Journal of Parasitology Research)
Background. Soil-transmitted helminths (STHs) and schistosome infections have been known to be major causes of morbidity and mortality in sub-Saharan countries. School aged and preschool children are known to be at high risk of infection. Therefore, the aim of this study was to determine the prevalence and risk factors associated with soil-transmitted helminths among school-going children in Lurambi Subcounty, Kakamega, Kenya. Method. A cross-sectional study was conducted from Jan 2020 to Feb 2020 among 392 randomly selected primary school-going children aged 5 to 14 years old in six primary schools. Risk factors associated with STH infection were obtained using a structured questionnaire answered by the children’s caregivers. Stool samples were examined using the standard quantitative Kato-Katz technique. The data was analyzed using SPSS version 20 and Epi Info version 7.2.3.1. Result. A total of 278 children provided stool samples for analysis. The overall prevalence of intestinal helminths was 14.4% (40/278). The prevalence of Ascaris lumbricoides was 11.5% (32/278), 0.4% (1/278) for hookworm, 0.4% (1/278) for Trichuris trichiura, and 2.1% (6/278) for Schistosoma mansoni; coinfection was detected in 0.4% (1/278). The intensity of infection ranged between light and moderate. Significant risk factors for STH infection included failure to wash hands before eating (OR: 3.529; P=0.041), failure to wash fruits and vegetables before eating (OR: 2.3129; P=0.005), and not washing hands after soil contact (OR: 2.1529; P=0.005). Age (Z=2.4006, P=0.0164) was a risk factor only for infection with Schistosoma mansoni. Conclusion. Preventive chemotherapy and proper hygienic and sanitation practices should be integrated to achieve elimination of STH and Schistosoma mansoni in Lurambi Subcounty and at large in Kenya.